Holocaust memory and cultural trauma: Israeli adolescents' poetry and heritage journeys to Poland. Issue 1 (2nd January 2020) - Gross, Zehavit
ABSTRACT: The objective of this research was to analyse poetry written by Israeli high-school students during or after visiting Poland within the framework of Holocaust education. I describe first the stages of shaping the discourse of Holocaust memory in Israel, and of Holocaust education; the Holocaust's place in the world of young Israelis; and the journeys to Poland as reflected in research. Following that, I present the results of the research and an analysis of the findings. The paper will discuss how Israeli adolescents cope with a cultural trauma.